2004
DOI: 10.1046/j.1540-8167.2004.03681.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Findings in Patients with Brugada Syndrome

Abstract: MRI Findings in Brugada Patients. Introduction: Cardiac magnetic resonance imaging (CMR) is a powerful diagnostic tool for evaluating cardiac structure and function. Recently, right ventricular wallmotion abnormalities were described using electron beam tomography in patients with Brugada syndrome. In the present study, we prospectively evaluated CMR findings in patients with Brugada syndrome compared to matched controls.Methods and Results: CMR was performed on 20 consecutive patients with proven Brugada synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 22 publications
(23 reference statements)
3
68
1
2
Order By: Relevance
“…20 Recent papers report an overlap between BS and arrhythmogenic RV cardiomyopathy, [21][22][23] and electron-beam computed tomography and magnetic resonance imaging in patients with BS has revealed localized morphologic abnormalities and fat infiltration in the RV. 24,25 Furthermore, recent papers de- scribe histopathologic changes such as myocarditis, hypertrophy, fibrosis and fatty infiltration, in the RV. [26][27][28] BS has been defined as an autosomal dominant disease with incomplete penetrance and has been linked to mutations in the SCN5A gene encoding for the -subunit of the cardiac sodium channel.…”
Section: Discussionmentioning
confidence: 99%
“…20 Recent papers report an overlap between BS and arrhythmogenic RV cardiomyopathy, [21][22][23] and electron-beam computed tomography and magnetic resonance imaging in patients with BS has revealed localized morphologic abnormalities and fat infiltration in the RV. 24,25 Furthermore, recent papers de- scribe histopathologic changes such as myocarditis, hypertrophy, fibrosis and fatty infiltration, in the RV. [26][27][28] BS has been defined as an autosomal dominant disease with incomplete penetrance and has been linked to mutations in the SCN5A gene encoding for the -subunit of the cardiac sodium channel.…”
Section: Discussionmentioning
confidence: 99%
“…Another contributor to the arrhythmic propensity may be the occurrence of structural changes in the heart tissue [Carlson et al, 1994;Meregalli et al, 2005]. The precise mechanism causing these has not, however, been clarified [Papavassiliu et al, 2004;Saffitz, 2005].…”
Section: Pathogenetic Mechanism-in Overviewmentioning
confidence: 99%
“…Recent reports indicated an overlap between Brugada syndrome and arrhythmogenic RV cardiomyopathy, [33][34][35] and electron-beam CT and magnetic resonance imaging in patients with Brugada syndrome have revealed localized RV morphologic abnormalities and fat infiltration. 36,37) Furthermore, recent articles reported histopathologic changes such as myocarditis, hypertrophy, fibrosis, and fatty infiltration in the RV. [38][39][40] An animal study also found that mutation in the gene encoding SCN5A in mice resulted in impairment of atrial and ventricular conduction associated with myocardial rearrangement and fibrosis.…”
Section: Discussionmentioning
confidence: 99%